Unexpected Loan Losses and Bank Capital in an Estimated DSGE Model of the Euro Area - Nikolay Hristov; Oliver Hülsewig (Center for Economic Studies and ifo Institute (CESifo), 2016)
We develop a stylized DSGE model in which banks face capital regulation and their loan portfolios are subject to non-diversifiable losses due to aggregate shocks. The framework is used to explore the importance of the interaction between macroeconomic conditions, credit default and bank capitalization for the transmission of macroeconomic shocks. We fit the model to euro area data. Impulse response analysis shows that the aforementioned interaction substantially magnifies the responsiveness of the economy to real and nominal demand side disturbances. The amplification is especially strong with respect to government spending shocks. The model is further capable of replicating two financial market characteristics that are documented in the empirical literature, i.e. the pro-cyclicality of bank profitability and the counter-cyclical response of firm default rates and credit spreads to monetary policy shocks.
Keywords: E44; E51; G21; G33; 330; DSGE model; bank capital; aggregate loan losses; business cycle fluctuations